Pengaruh Media Gambar dan Motivasi Belajar Terhadap Kemampuan Menulis Teks Eksposisi Siswa Kelas X MAN 1 Bandar Lampung Tahun Pelajaran 2021/2022 - Riya Septiyana (LPPM STKIP PGRI Bandar Lampung, 2022)
This study uses a quantitative approach with a quasi-experimental type of research with a 2x2 factorial design. Data collection techniques with objective description tests of the ability to write exposition texts and learning motivation questionnaires. The collected data were statistically processed using a two-way analysis of variance (ANVA) technique with a significance level of 0.05. The results showed that: (1) The ability to write expository texts of students who were taught using picture media got the highest score of 95 and an average of 79.86, while the use of conventional media got the highest score of 89 and an average of 76.97. (2) There is an interaction between learning strategies and learning motivation on learning outcomes as evidenced by the acquisition of the value fh = 5.6 > ft = 3.98. (3) the ability to write expository texts of students who are taught using picture media and have high motivation got the highest score of 95 and an average of 84.40, while those who used conventional media got the highest score of 87 and an average of 75.58, (4) ability In writing expository texts, students who are taught using image media and have low motivation with conventional media have differences. The ability to write expository texts of students who are taught using picture media and have low motivation gets an average score of 75.31 and conventional media 76.37.